Rye (Secale cereale L.) revisited—nutritional composition, functional benefits, and role in sustainable diets - Zadeike, Daiva; Copperstone, Claire; Aleksandrova, Olha; Ünal, Derya Özalp; Šavikin, Katarina; Živković, Jelena; Güzel, Mustafa; Kalkan Yildirim, Hatice; Künili, Ibrahim Ender; Ivanova, Teodora; Özmen, Özge; Bantis, Filippos; et al. (Frontiers in Nutrition, 2025)
Rye (Secale cereale L.) is increasingly recognized as a sustainable cereal with significant nutritional, ecological, and economic potential. While previous studies have highlighted its dietary fiber (DF), bioactive compounds, and associated health benefits, this review provides an updated synthesis that integrates recent findings on rye's role in human health, food security, and sustainability. In particular, it emphasizes novel evidence on rye's functional properties, its potential contributions to plant-based dietary strategies, and its economic and social relevance. By consolidating current knowledge and outlining future directions for product development and dietary innovation, this work offers a fresh perspective that extends beyond earlier 0 reviews focused on rye.